Digestão anaeróbia das frações da cama de frango - Silva, Laíza Cavalcante de Albuquerque (2019)
Poultry litter (PL) is the waste generated from growing and fattening poultry, and its final destination is responsibility of the poultry farmer due to the integration system adopted by the great majority of farms in Brazil. Due to the cost for its acquisition, the PL has been reused several times, which has changed mainly its chemical characteristics, due to the addition of excrements and poultry feed to its composition. To mitigate environmental liabilities, PL must be stabilized before being disposed in the soil as a conditioner or used as source of nutrients. The anaerobic digestion process is an alternative for the stabilization of PL with the possibility of energy and nutrient recovery. However, AD in horizontal tubular reactors, more common in Brazil, requires the dilution of PL, given its physical characteristics. Therefore, different PL dilutions in water were initially studied (1: 4; 1: 6; 1: 8; 1:10 and 1:12). In addition to the dilution test, the PL was subjected to physical fraction separation pretreatment, followed by a mass balance to quantitatively characterize the liquid, solid (sieve retained) and intact (no separation) fractions. Subsequently, the different fractions were subjected to a biochemical methane potential (BMP) test following VDI-4630 standards. Finally, a semicontinuous feeding trial was carried out with the treatment that presented the most adequate results, testing the use of 40% digestate recycle in the dilution of PL. Mass balance was important to determine the dilutions used for the BMP test, in which the 1:6, 1:8, and 1:10 dilutions were used. Although containing the largest amount of volatile solids, the fraction retained in the sieve did not have the highest potentials, due to the carbon’s recalcitrant characteristic. The highest potential obtained was observed in the 1:6 dilution liquid fraction, followed by the 1:8 integral dilution fraction, with potentials of 215.96 and 198.28 liters CH4 / kg SV added, respectively. The results obtained by conducting the semicontinuous feeding trial showed that the use of 40% recycle for PL dilution had no inhibitory effect on AD process, reaching 83.12 and 78.59 liters CH4 / kg SV added with and without recycling, respectively. Despite a lower numerical value of production using recycle, this was not statistically different, with the advantage of providing the producer with a 40% savings in the use of clean water to dilute the PL, reducing production costs and providing a digestate with higher nitrogen content, one of the nutrients most required by most crops.